2022
DOI: 10.3389/fphar.2022.955701
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic injury following immune checkpoint inhibitors: A systematic review and meta-analysis

Abstract: Background: Pancreatic injury (pancreatitis, amylase/lipase elevation) is a rare adverse event of immune checkpoint inhibitors (ICIs). With the high number of clinical studies on ICIs, the incidence and characteristics of associated pancreatic injury (PI) need to be reevaluated.Methods: A systematic review and meta-analysis was conducted to assess the incidence of PI in cancer patients who received ICIs in randomized controlled trials (RCTs). PubMed, Embase, the ASCO, ESMO, and AACR conference proceedings befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…Some studies have reported on the risk factors for ICI-PI [ 16 , 17 , 19 , 32 ]. George et al reported that CTLA-4 inhibitors, combination therapy, and malignant melanoma were high-risk factors for ICI-PI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported on the risk factors for ICI-PI [ 16 , 17 , 19 , 32 ]. George et al reported that CTLA-4 inhibitors, combination therapy, and malignant melanoma were high-risk factors for ICI-PI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the administration of ICIs is associated with immune-related adverse events (irAEs), which commonly involve the dermatologic, gastrointestinal, hepatic, pulmonary, and endocrine systems [11,12] and their management has been established [13,14]. However, pancreatic injuries are rare irAE manifestations of ICI administration [15][16][17][18][19][20], and their incidence, risk factors, treatments, clinical course, and associated OS are unclear. The National Comprehensive Cancer Network (NCCN) guidelines recommend continuation of ICI therapy in asymptomatic patients with pancreatic enzyme elevation with normal findings on pancreatic imaging [21].…”
Section: Introductionmentioning
confidence: 99%
“…ICI-induced immunoassociated pancreatitis is currently a major area of focus in this field, which is a relatively uncommon irAE but has a high likelihood of being severe (≥ grade 3) [ 36 ] and potentially fatal [ 37 ]. It is characterized by serum amylase or lipase values greater than 3 times the upper limit of the normal value [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the inflammatory status of ir exocrine pancreatitis triggers immune sensitization, which, in turn, may increase the risk of islet autoimmunity, but this hypothesis is unexplored [10,85]. Overall, due to the rarity of both irDM and ir pancreatitis, the explicit mechanisms underlying ir pancreatitis, irDM, and the interrelationship thereof remain elusive.…”
Section: The Potential Involvement Of Pancreatic Alpha (α) Cells and ...mentioning
confidence: 99%